Ohmic heating technology for food processing: a review of recent developments - Jan, Bisma; Shams, Rafeeya; Rizvi, Qurat Ul Eain Hyder; Manzoor, Arshied (Journal of Postharvest Technology)
The novel technique of heating that utilizes the natural electrical resistance of the food material to produce heat and where electrical energy is converted into thermal energy is called ohmic heating. It can be considered as efficient and alternating thermal processing technology wherein food sample is placed between electrodes having a role of resistance in the circuit. This process involves heating of food by passing electric current throughout materials. Ohmic heating has a good capability to achieve fast and consistent heating in food materials, resulting in microbiologically secure and better quality foods. Compared to traditional heating techniques, this process has lesser heating durations while preventing hot surfaces and could decrease temperature gradients. Ohmic heating presents a broad range of vital applications like extraction, fermentation, cooking, evaporation, thawing, pasteurization, sterilization, aseptic processing, blanching, semi meatball cooking and drying process. This process results in minimal structural changes in product configuration and hence the nutritional value is preserved and yields exceptional processed quality food products in lesser operating time. This is uniform and rapid heating method where the heating rate depends solely on the field strength electrical conductivity. It is very essential to have the vital knowledge of mathematical models of ohmic heating and electrical conductivity of food materials in order to design the ohmic process optimally.